Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Suasana Kafe Terhadap Kepuasan Pelanggan di Arus Balik Coffee And Space Kota Semarang - Eni Lutfiani; Nurdiyanto, Ahmad Dwi; Mohamad Toha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The objectives of this research is knowing and explaining the influence of product quality, service quality, café atmosphere on customer satisfaction at the Arus Balik Coffee and Space in Semarang City. The population in this research is the general public, both those living in Semarang City and outside Semarang City who make purchases at the Arus Balik Coffee and Space cafe. The research was carried out by sampling using a purposive sampling technique and the number was determined using the Lemeshow formula because the target population was too large and the numbers changed. A sample of 96 respondents was obtained. Research data was obtained through questionnaires given to respondents. Next, testing was carried out on the data including instrument testing using validity tests and reliability tests. Then analyzed using multiple linear regression, F test, and individual test (t test) with SPSS 25. The research results can be concluded that: 1) Product quality has a positive and significant effect on customer satisfaction, 2) Service quality has a positive and significant effect on customer satisfaction, and 3) Cafe atmosphere has a positive and significant effect on customer satisfaction.